Hyaluronate activation of CD44 induces insulin-like growth factor-1 expression by a tumor necrosis factor-alpha-dependent mechanism in murine macrophages. - Noble, P W (1993)
Macrophages participate in inflammatory and repair processes in part through the selective release of cytokines that contribute to tissue remodeling. Extracellular matrix components generated at inflammatory sites may influence tissue remodeling by effects on leukocyte adherence and local cytokine production. In murine bone marrow-derived macrophages, we found that soluble hyaluronic acid stimulated IL-1 beta, TNF alpha, and insulin-like growth factor-1 (IGF-1) mRNA transcript expression as well as IGF-1 protein synthesis. Monoclonal antibodies to the hyaluronic acid receptor CD44 blocked the effects of hyaluronic acid on IL-1 beta, TNF alpha, and IGF-1 expression. TNF alpha and IL-1 beta mRNA expression preceded IGF-1 protein synthesis, and TNF alpha, but not IL-1 beta, was found to directly stimulate IGF-1. Furthermore, IGF-1 induction was dependent on endogenous TNF alpha production since IGF-1 protein synthesis was inhibited in the presence of anti-TNF alpha antiserum. In addition, IL-1 beta was found to exert a regulatory role on IGF-1 production by enhancing the TNF alpha effect. IL-1 beta and TNF alpha mRNA transcript expression as well as IGF-1 protein synthesis were also stimulated by chrysotile asbestos. Anti-CD44 antibodies had no effect whereas anti-TNF alpha antiserum blocked asbestos-stimulated IGF-1 production. These results indicate that hyaluronate activation of CD44 induces cytokine expression and macrophage-derived IGF-1 production is dependent on TNF alpha expression.